Chemometric perspectives on plankton community responses to natural iron fertilisation over and downstream of the Kerguelen Plateau in the Southern Ocean - Trull, TW; Davies, DM; Dehairs, F; Cavagna, AJ; Lasbleiz, M; Laurenceau-Cornec, EC; D'Ovidio, F; Planchon, F; Leblanc, K; Queguiner, B; Blain, S (Biogeosciences, 2015)
We examined phytoplankton community responses to natural iron fertilisationat 32 sites over and downstream from the Kerguelen Plateau in the SouthernOcean during the austral spring bloom in OctoberNovember 2011. The communitystructure was estimated from chemical and isotopic measurements (particulateorganic carbon POC; 13 C-POC; particulate nitrogen PN; 15 N-PN; andbiogenic silica BSi) on size-fractionated samples from surface waters (300,210, 50, 20, 5, and 1 μm fractions). Higher values of 13 C-POC (vs.co-located 13 C values for dissolved inorganic carbon DIC) were takenas indicative of faster growth rates and higher values of 15 N-PN (vs.co-located 15 N-NO 3 source values) as indicative of greater nitrateuse (rather than ammonium use, i.e. higher f ratios). Community responses varied in relation to both regional circulation and theadvance of the bloom. Iron-fertilised waters over the plateau developeddominance by very large diatoms (50210 μm) with high BSi / POC ratios,high growth rates, and significant ammonium recycling (lower f ratios) asbiomass built up. In contrast, downstream polar frontal waters with a similaror higher iron supply were dominated by smaller diatoms (2050 μm)and exhibited greater ammonium recycling. Stations in a deep-waterbathymetrically trapped recirculation south of the polar front with loweriron levels showed the large-cell dominance observed on the plateau butmuch less biomass. Comparison of these communities to surface water nitrate(and silicate) depletions as a proxy for export shows that the low-biomassrecirculation feature had exported similar amounts of nitrogen to the high-biomass blooms over the plateau and north of the polar front. This suggeststhat early spring trophodynamic and export responses differed betweenregions with persistent low levels vs. intermittent high levels of ironfertilisation.